The Effect of Work-Life Balance and Work Environment on Organizational Commitment with Job Satisfaction as a Mediator at Ananda Purwokerto Hospital - Tiarto, Ahlan Gema; Widhiandono, Hengky; Suyoto, Suyoto; Innayah, Maulida Nurul (PT FORMOSA CENDEKIA GLOBAL, 2025)
This study investigates the influence of work-life balance and work environment on organizational commitment, with job satisfaction as a mediating variable, at Ananda Purwokerto General Hospital. Using a quantitative approach, data were collected from 130 healthcare workers selected through accidental sampling. The Slovin formula with a 5% margin of error was used to determine the sample size. Data analysis was conducted using Structural Equation Modeling (SEM) with the Partial Least Squares (PLS) approach via SmartPLS 4.0 software. The results show that work-life balance and work environment both have a positive and significant effect on job satisfaction and organizational commitment. Moreover, job satisfaction significantly influences organizational commitment and mediates the relationship between work-life balance, work environment, and organizational commitment.